Implementasi E-LKPD Liveworksheets Melalui Google Classroom terhadap Pemahaman Konsep IPA Peserta Didik Kelas VIII - Nurkhalifah Febrianty Syah; Sitti Rahma Yunus; Sitti Saenab (Celebes Science Education, 2025)
The reaserch aims to the level of understanding of students' science concepts before and after implementing E-LKPD Liveworksheets through Google Classroom, increasing students' understanding of science concepts after implementing E-LKPD Liveworksheets through Google Classroom, understanding of science concepts of grade VIII MTs DDI Gusung Makassar students significantly increased after implementing E-LKPD Liveworksheets through Google Classroom. The population of this study was all grade VIII students at MTs DDI Gusung Makassar with samples selected using purposive sampling techniques so that the sample in the study was 25 students. The research instrument uses the implementation of E-LKPD Liveworksheets through Google Classroom with 25 questions in the form of multiple choice and divided into 3 indicators of understanding, namely translation, interpretation, and extrapolation. Based on the results of data analysis, it is known that: (1) The level of understanding of the concept of grade VIII MTs DDI Gusung students before the implementation of Google Classroom-based E-LKPD Liveworksheets on Business and Simple Aircraft materials in everyday life is in the category of lacking, (2) The level of understanding of the concept of grade VIII MTs DDI Gusung students after implementing Google Classroom-based E-LKPD Liveworksheets on Business and Aircraft material in everyday life is in the very good category, (3) Increased understanding of the concepts of grade VIII MTs DDI Gusung students after implementing Google Classroom-based E-LKPD Liveworksheets on Business and Aircraft material in everyday life is in the high category. (4) The understanding of science concepts of grade VIII MTs DDI Gusung Makassar students significantly improved after the implementation of E-LKPD Liveworksheets through Google Classroom.